Ambient chemical fixation of CO2 using a highly efficient heterometallic helicate catalyst system. Issue 18 (16th January 2018) - Wang, Li; Xu, Cong; Han, Qingxin; Tang, Xiaoliang; Zhou, Panpan; Zhang, Ruilian; Gao, Guoshu; Xu, Benhua; Qin, Wenwu; Liu, Weisheng
Abstract : Two novel heptanuclear 3d–4f helicates have been synthesized and characterized. Abstract : Two novel heptanuclear 3d–4f helicates have been synthesized and characterized. The helicates act as catalysts and show high catalytic activity for the coupling of CO2 and epoxides to obtain cyclic carbonates with a wide substrate scope at ambient temperature and pressure.